Preventing delayed diagnosis of cancer: clinicians’ views on main problems and solutions - Car, Lorainne Tudor (2018)
Background Delayed diagnosis is a major contributing factor to the UK’s lower cancer survival compared to many European countries. In the UK, there is a significant national variation in early cancer diagnosis. Healthcare providers can offer an insight into local priorities for timely cancer diagnosis. In this study, we aimed to identify the main problems and solutions relating to delay cancer diagnosis according to cancer care clinicians. Methods We developed and implemented a new priority–setting approach called PRIORITIZE and invited North West London cancer care clinicians to identify and prioritize main causes for and solutions to delayed diagnosis of cancer care. Results Clinicians identified a number of concrete problems and solutions relating to delayed diagnosis of cancer. Raising public awareness, patient education as well as better access to specialist care and diagnostic testing were seen as the highest priorities. The identified suggestions focused mostly on the delays during referrals from primary to secondary care. Conclusions Many identified priorities were feasible, affordable and converged around common themes such as public awareness, care continuity and length of consultation. As a timely, proactive and scalable priority–setting approach, PRIORITZE could be implemented as a routine preventative system for determining patient safety issues by frontline staff.